Co-designing a recruitment strategy for lung cancer screening in high-risk individuals: protocol for a mixed-methods study [version 2; peer review: 1 approved, 2 approved with reservations] - Nicole Rankin; Brona Mulligan; Kate Brain; Patrick Redmond; Sam McGlynn; Grace McCutchan; Conor Murphy; Mohammed Alam; Ahmeda Ali; Frank Doyle; Maeve Reilly; Laura Heavey; et al. (HRB Open Research, 2025)
Background Lung cancer is a significant cause of cancer-related mortality globally, with early detection through screening critical to improving patient outcomes. However, recruiting high-risk individuals, particularly in deprived populations, for screening remains a considerable challenge. This study aims to co-design a targeted recruitment strategy for lung cancer screening, tailored to the specific needs and experiences of high-risk individuals, in collaboration with a Patient and Public Involvement (PPI) panel and expert stakeholders in Ireland. Methods We will employ a mixed-methods design guided by the Medical Research Council (MRC) framework for developing complex interventions. Our approach will integrate systematic review findings on screening participation interventions, evaluation of the recruitment strategy's feasibility in an Irish context, and the application of behavioural science frameworks. The target population includes individuals aged 55–74 who reside in highly deprived areas and are at high risk of developing lung cancer based on the National Lung Screening Trial criteria, as well as those eligible for our Lung Health Check trial who met equivalent risk thresholds. Conclusion This co-designed recruitment strategy will combine evidence-based research, local context understanding, and stakeholder input to develop a solution that is both scientifically robust and tailored to the target population's needs. This patient-centred approach aims to increase the potential for successful implementation of lung cancer screening programs, thereby improving early detection and patient outcomes.